Hot Extrusion Effect on the Microstructure and Mechanical Properties of a Mg–Y–Nd–Zr Alloy - Sheng, L.Y.; Du, B.N.; Wang, B.J.; Xu, D.K.; Lai, C.; Gao, Y.; Xi, T.F. (Проблемы прочности, 2018)
A Mg–Y–Nd–Zr alloy was prepared by casting and hot extrusion. The microstructure and mechanical properties of OM, SEM, XRD, TEM, and tensile tests were investigated with casting and hot extruded alloys. The results demonstrate that in a casting Mg–Y–Nd–Zr alloy, the α-Mg matrix is separated into the cell structure by a discontinuously distributed coarse Mg₂₄Y₅/α-Mg eutectic structure and fine Mg₁₂Nd particles. Сплав Mg-Y-Nd-Zr получен литьем и горячей экструзией. Исследованы микроструктура и механические свойства литейного и экструзионного сплавов с помощью оптической, сканирующей электронной, просвечивающей электронной микроскопии, рентгенографии и испытаний на растяжение. Показано, что матрица α-Mg в литейном сплаве превращается в ячеистую структуру за счет образования дискретно распределенной крупной эвтектики Mg₂₄Y₅ и мелких частиц Mg₁₂Nd/α-Mg.